SISTEM AKUNTANSI KLAIM HABIS KONTRAK PADA ASURANSI JIWA BERSAMA BUMIPUTERA 1912 CABANG UJUNG TANAH MAKASSAR - Nur Fadny Yuliani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
The purpose of this research was to know how accounting system for contract expired claims at AJB Bumiputera 1912 Branch Office of Ujung Tanah Makassar, contraints in the system of accounting for contract expired claims and efforts made to overcome the obstacles faced. The type and design in this study used a descritive qualitative type, namely knowing, explaining and describing the accounting system for contract expired claims in AJB Bumiputera 1912 Branch Office of Ujung Tanah Makassar. The program payment of claims through centralization. Finance Department pays immediately to the bank account of the policy holder or recipient of insurance benefit. Recording system payment of contract expiration claim using a computerized system The result showed that accounting system of contract expired claims already has accounting records accordance to their needs. It can be seen that the fractions has worked according to their duties. While the problems that are experienced in the accounting system for contract expired claims, are: lack of supervision on customer premium payments, where there are some customers who are negligent in carrying out their obligations in paying insurance premiums which result in the payment of contract expired claims not due. For this reason, it is necessary to review the system used so that the documents used are in accordance with the needs, and there is no abuse, fraud and the results can be more effective. The efforts to overcome the obstacles in the accounting system for contract expired claims are that the KUAK section (Head of Administrative and Finance Unit) conducts a routine check of premium payment receipts to avoid paying out-of-contract expired claims and sending an official notification letter from the company to the customer that the contract period will expire.